Ticagrelor vs. clopidogrel for coronary microvascular dysfunction in patients with STEMI: a meta-analysis of randomized controlled trials - Li, Yike; Ye, Zixiang; Guo, Ziyu; Xie, Enmin; Wang, Min; Zhao, Xuecheng; Liu, Mei; Li, Peizhao; Yu, Changan; Gao, Yanxiang; Zheng, Jingang (Frontiers in Cardiovascular Medicine, 2023)
Purpose: About half of ST-elevation myocardial infarction patients undergoing revascularization present with coronary microvascular dysfunction. Dual antiplatelet therapy, consisting of aspirin and a P2Y12 inhibitor (clopidogrel or ticagrelor), is recommended to reduce cardiovascular event rates after ST-segment elevation myocardial infarction (STEMI). The aim of the current study was to perform a pooled analysis of randomized controlled trials (RCTs) to compare the effects of ticagrelor and clopidogrel on coronary microcirculation dysfunction in STEMI patients undergoing primary percutaneous coronary intervention. Methods: PubMed, Embase, Cochrane Library, and Web of Science database were searched for eligible RCTs up to September 2022, with no language restriction. Coronary microcirculation indicators were: corrected TIMI frame count (cTFC), myocardial blush grade (MBG), TIMI myocardial perfusion grade (TMPG), coronary flow reserve (CFR), and index of microcirculatory resistance (IMR). Results: Seven RCTs involving a total of 957 patients (476 treated with ticagrelor and 481 treated with clopidogrel) were included. Compared with clopidogrel, ticagrelor better accelerated the microcirculation blood flow: cTFC (-2.40; 95% CI: -3.38 to -1.41, p < 0.001) and improved myocardial perfusion: MBG = 3 (OR 1.99; 95% CI: 1.35 to 2.93, p < 0.001) and MBG ≥ 2 (OR 2.57; 95% CI: 1.61 to 4.12, p < 0.001). Conclusions: Ticagrelor has more benefits for coronary microcirculation than clopidogrel in STEMI patients undergoing primary percutaneous coronary intervention (PCI). Therefore, it is recommended that it be administered in this setting.